Computer Society Announces 2009 Program Lineup. (Computer (00189162), 2009)
This article discusses the work of the Institute for Electrical and Electronic Engineers Inc. (IEEE) Computer society during 2009. The benefits of membership, including a subscription to this journal, access to the Computer Society Digital Library, and volunteer editorial service opportunities are noted. Continuing education programs offered by the IEEE are presented. Conferences including the IEEE Virtual Reality 2009 conference in Lafayette, Louisiana from March 14-18, the IEEE Security and Privacy 2009 from May 17-20 in Berkeley, California, and Cool Chips XII from April 15-17 in Yokohama, Japan are described.